Democratic Discipline over the Soldiers: The Post-2004 Dynamic Mapping of Civilian Control over the Military in Indonesia (Universitas Terbuka, 2023)
This article attempts to explain the development map of the quality of democratic control over the military in Indonesia from 2004 to the second period of Joko Widodo’s administration. Some of the questions that will try to ontrol are, why did the president with a retired military general background be considered as having the modality in building a civilian ontrol over the military after the Reformation? And how was the institutionalization of civilian control over the military? This study was conducted based on a literature study and news analysis about civilian control over the military since 2004. The year 2004 was a turning point in the dynamics of civil-military relations in Indonesia to find its ideal form in the context of capable civilian control over the military, after more than three decades involvement of military groups into Indonesian politics throughout the New Order era. At the beginning of the Reformation era, the civilian government at that time was still not paying serious attention on efforts to subordinate military groups under civilian rule, resulting in uncondusive observations of civil-military relations in the first years of the Reformation. The euphoria of the Reformation tend to direct civil attention to the issues of post-New Order political institutionalization, until finally Indonesia was only able to organize a viable electoral system in 2004, which at that time was won by presidential pairs of Susilo Bambang Yudhoyono (SBY) and vice president Jusuf Kalla ( JK). The elected President, SBY as the only president in the Reformation era with a retired military general background is considered to be a modality to stop the confusion of civilian government attitudes towards military groups in Indonesia in building civil supremacy over the military. However, the success of civilian control over the military still rests on the personal power of the head of state rather than as a result of the institutionalization of an established civilian control scheme over the military.